In vitro Cytotoxicity and Pharmacokinetic Evaluation of Pharmacological Ascorbate in Dogs - Musser, Margaret L.; Mahaffey, Alyssa L.; Fath, Melissa A.; Buettner, Garry R.; Wagner, Brett A.; Schneider, Benjamin K.; Seo, Yeon-Jung; Mochel, Jonathan P.; Johannes, Chad M. (Frontiers in Veterinary Science, 2019)
Background: High-dose, pharmacological ascorbate (P-AscH-) is preferentially cytotoxic to human cancer cells in vitro. Investigations on the efficacy of P-AscH- as an adjuvant treatment for multiple human cancers are on-going, but has yet to be formally investigated in dogs. The primary objectives of this study were to determine the pharmacokinetic (PK) profile of P-AscH- in healthy Beagle dogs and the effects of P-AscH- on canine osteosarcoma cells in vitro. Methods: Eight purpose-bred, healthy, spayed female Beagle dogs, between 20 and 21 months old, and 8 to 10 kg were administered two doses of P-AscH- (550 mg/kg or 2200 mg/kg) via intravenous infusion over six hours, on separate days. Plasma ascorbate concentrations were measured at 12 time points during and after infusion for PK analysis using nonlinear mixed-effects (NLME) and non-compartmental analysis (NCA). Clonogenic assays were performed on 2 canine osteosarcoma cell lines (D-17 and OSCA-8) and canine primary dermal fibroblasts after exposure to high concentrations of ascorbate (75 pmoles/cell). Results: Plasma ascorbate levels in the dogs peaked at approximately 10 mM following 2200 mg/kg and returned to baseline 6 - 8 h after dosing. Minor adverse effects were seen in 2 dogs. Ascorbate (75 pmoles/cell) significantly decreased survival in both the osteosarcoma cell lines (D-17 63% SD .010, P = .005; OSCA-8 50% SD .086, P = .026), compared to normal fibroblasts (27% SD .056). Conclusions: Pharmacological ascorbate is preferentially cytotoxic to canine-derived cancer cells. High levels of ascorbate can be safely administered to dogs. Further studies are needed to determine the effects of P-AscH- on canine patients.